Ergonomy of Bus Entry-Exit Access for Elderly Hajj Pilgrims in Surabaya Embarkation Group 2023 - Rabbani, Naufal; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v2i0.3236, 2024)
The implementation of hajj pilgrimage in 1444 H/2023 AD in Indonesia was quite unique, the Ministry of Religion Affairs echoed message “Fairness and Friendly for Elderly Hajj”. In line with the message, everything in organizing this hajj needs to be adapted with anatomy and physiological abilities of the elderly. In this study, we observe the specifications of 4 buses specifically to transport elderly hajj pilgrims who at risk of falls and disable from Surabaya Embarkation Hajj Dormitory to Juanda Embarkation Airport.  Direct observation and measurement for aspects of door height, door width, step height, ramp height, ramp inclined length, stanchion height, stanchion length, handrail height, handrail length. The observation results show that in general entry and exit access for passengers the four buses does not meet the specification criteria for creating ergonomics for elderly Hajj pilgrims.